Humanimal : how Homo sapiens became nature's most paradoxical creature : a new evolutionary history - Rutherford, Adam (New York : The Experiment, 2019)
"Evolutionary theory has long established that humans are animals: Modern Homo sapiens are primates who share an ancestor with monkeys and other great apes. Our genome is 98 percent identical to a chimpanzee s. And yet we think of ourselves as exceptional. Are we? In this original and entertaining tour of life on Earth, Adam Rutherford explores the profound paradox of the human animal. Looking for answers across the animal kingdom, he finds that many things once considered exclusively human are not: In Australia, raptors have been observed starting fires to scatter prey; in Zambia, a chimp named Julie even started a fashion of wearing grass in one ear. We aren t the only species that communicates, makes tools, or has sex for reasons other than procreation. But we have developed a culture far more complex than any other we ve observed. Why has that happened, and what does it say about us? [This book] is a new evolutionary history a synthesis of the latest research on genetics, sex, migration, and much more. It reveals what unequivocally makes us animals and also why we are truly extraordinary"--
Originally published in Great Britain by Weidenfeld & Nicolson in 2018 under the title: The book of humans.
Includes bibliographical references (pages 219-230) and index.
Keywords: Human evolution -- Popular works